Mosquitocidal activities of thyme oils (Thymus vulgaris L.) against Culex quinquefasciatus (Diptera: Culicidae) - Pavela, Roman; Vrchotová, Nadezda; Tríska, Jan (Parasitology research, 2009)
Oil samples from four chemotypes of Thymus vulgaris were tested for mosquitocidal activity. Oil compounds were analyzed by gas chromatography-mass spectrometry (GC-MS). The different compositions of the oils varied in their biological activity as well. Larvicidal efficiency was determined for the most significant oil thymol type (T), namely the lowest doses LD(50) 32.9 and 14.2 mg/l for the third and fourth instars, respectively. The oils also showed very good efficiency with respect to mortality and to the percentage of adult emergence upon short-term exposure in water treated by lethal doses of individual oils. Although the larvae were left in treated water for only 5 h, mortality corresponding to LD(50) was determined after 24 h, i.e., between 49% and 63%. Furthermore, mortality increased significantly in relation to time of exposure, and total mortality of the larvae at the end of their development was about 90%. Such significant mortality was also naturally reflected in the total emergence of adults. In the control sample, there was 77% adult emergence from the larvae, whereas in oils, there was only from 5.3% to 16% emergence. The greatest fumigate efficiency was found for T and linalool chemotypes, with an LC(50) for 24 h of exposure being 1.1 and 1.8 mg/l, respectively. Essence T was also most efficient in the tarsal test, with LD(50) of 44 microg/cm(2) and LD(90) of 63 microg/cm(2). High antioviposition efficiency was found in all tested oils.
Keywords: Thymus Plant; analýza přežití; Survival Analysis; Time Factors; Fumigation; Insecticides; vykuřování; Culex; Thymus (rostlina); ženské pohlaví; zvířata; Lethal Dose 50; plynová chromatografie s hmotnostně spektrometrickou detekcí; časové faktory; larva; insekticidy; Larva; LD50; Female; Plant Oils; Gas Chromatography-Mass Spectrometry; oleje rostlin; Animals